An introduction to overviews of reviews: planning a relevant research question and objective for an overview - Harriet Hunt (Systematic Reviews, 2018)
Abstract Background Overviews of systematic reviews are a relatively new approach to synthesising evidence, and research methods and associated guidance are developing. Within this paper we aim to help readers understand key issues which are essential to consider when taking the first steps in planning an overview. These issues relate to the development of clear, relevant research questions and objectives prior to the development of an overview protocol. Methods Initial discussions and key concepts for this paper were formed during a workshop on overview methods at the 2016 UK Cochrane Symposium, at which all members of this author group presented work and contributed to wider discussions. Detailed descriptions of the various key features of overviews and their different objectives were created by the author group based upon current evidence (Higgins J, Green S. Cochrane Handbook Syst Rev Interv. 2011;4:5, Pollock M, et al. Sys Rev. 2016;5:190-205, Pollock A, et al. Cochrane overviews of reviews: exploring the methods and challenges. UK and Ireland: Cochrane Symposium; 2016, Pieper D, et al. Res Syn Meth. 2014;5:187–99, Lunny C, et al. Sys Rev. 2016;5:4-12, Hartling L, et al. Comparing multiple treatments: an introduction to overviews of reviews. In 23rd Cochrane Colloquium; 2015, Hartling L, et al. Plos One. 2012;7:1-8, Ballard M, Montgomery P. Res Syn Meth. 2017;8:92-108) and author experiences conducting overviews. Results Within this paper we introduce different types of overviews and suggest common research questions addressed by these overviews. We briefly reflect on the key features and objectives of the example overviews discussed. Conclusions Clear decisions relating to the research questions and objectives are a fundamental first step during the initial planning stages for an overview. Key stakeholders should be involved at the earliest opportunity to ensure that the planned overview is relevant and meaningful to the potential end users of the overview. Following best practice in common with other forms of systematic evidence synthesis, an overview protocol should be published, ensuring transparency and reducing opportunities for introduction of bias in the conduct of the overview.